Situation Report: Romania, 24 May 1974 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Further Changes in the Romanian Press Coverage of French Presidential Elections Reaction to Maalot [Ma'alot] Massacre Relations with Portugal New Developments in Foreign Trade Macovescu's Visit to Belgium, Luxembourg, Italy, the Vatican, and Switzerland